Perjanjian Kredit Pada Bank BTPN Ditinjau Dari Asas Kebebasan Berkontrak - Dian Saputra Sinaga, Budi Santoso, Ery Agus Priyono (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
In Law no. 10 of 1998 concerning Amendment to Law no. 7 of 1992 concerning Banking is the bank described the entities that raise funds from the public in the form of savings and channel them to the public in the form of loans and / or other forms in order to improve the standard of living of the people. BTPN Apex is one of the banks that participated actively in economic activities by providing credit. The existence of credit lead to a credit agreement. Where clauses contained in the credit agreement had been predetermined by the bank as a creditor and the debtor will only be consulted, whether to accept or not the conditions set out in the form. This makes the customer has no choice but to agree to the terms that have been made by the bank. Based on the results of research and discussion, it can be concluded that the implementation of the credit agreement remains possible flexibility of the clause set BTPN, among others, in determining the loan amount, duration and magnitude of interest rate payments. While the obstacles faced due to lack of liver-heart banks provide credit and also increase the prices of goods that can lead to unhealthy conditions of the customer's business, which can cause bottlenecks in the repayments.